Shattering the black box: Technicities of architectural manipulation. (December 2018) - Kousoulas, Stavros
This article attempts to reverse a fallacy often met in architectural theories and practices: that of a supposed input which through processes of what one can broadly call translations generates a built output. The input–output fallacy produces an architectural black box that treats both architectural thinking and doing as a mere process of projecting, representing and annotating 'properly' what will later be executed. On the contrary, a manipulative account of architecture as an active process of ecological engineering will pave the way for not only reversing the fallacy but also towards a particular understanding of architectural practices: architectural technicities and their reticular, affective potentials. Drawing on the theories of Gilbert Simondon, André Leroi-Gourhan, Gilles Deleuze and Felix Guattari, I will examine how architecture can be genealogically approached as a reticular technicity which evolves by a reciprocal concretisation of its technical objects and a generalisation of its active practitioners: no longer the application of transcendental design rules, of symbolic deductions or statistical inductions but rather abductive heuristics of affective techniques; no input nor output but practices of sensorial amplification via material manipulation and vice versa.